2004
DOI: 10.1128/iai.72.5.3011-3021.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 and the Actin-Related Protein/Neural Wiskott-Aldrich Syndrome Protein Network Mediate Cellular Invasion by Cryptosporidium parvum

Abstract: Cryptosporidium parvum invasion of epithelial cells involves host cell membrane alterations which require a remodeling of the host cell actin cytoskeleton. In addition, an actin plaque, possibly associated with the dense-band region, forms within the host cytoplasm at the host-parasite interface. Here we show that Cdc42 and RhoA, but not Rac1, members of the Rho family of GTPases, are recruited to the host-parasite interface in an in vitro model of human biliary cryptosporidiosis. Interestingly, activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 46 publications
2
43
0
Order By: Relevance
“…The formation of AQP9-induced filopodia was reduced by cotransfection with an inhibitory GTP-Cdc42-binding N-WASP CRIB synthetic analog [Loitto et al, 2007]. Further support for a Cdc42-AQP interaction comes from observations of a direct localization of Cdc42 to AQP1-enriched domains, shown in C parvum-induced membrane protrusions [Chen et al, 2004]. So, how is Cdc42 associated with the PKC activation/binding discussed above?…”
Section: Aqp9 Cdc42 and Pkcfmentioning
confidence: 88%
“…The formation of AQP9-induced filopodia was reduced by cotransfection with an inhibitory GTP-Cdc42-binding N-WASP CRIB synthetic analog [Loitto et al, 2007]. Further support for a Cdc42-AQP interaction comes from observations of a direct localization of Cdc42 to AQP1-enriched domains, shown in C parvum-induced membrane protrusions [Chen et al, 2004]. So, how is Cdc42 associated with the PKC activation/binding discussed above?…”
Section: Aqp9 Cdc42 and Pkcfmentioning
confidence: 88%
“…In accordance with previous reports (14,37) The mechanisms by which FasL is translocated to the membrane and released from infected cells are unclear and currently under investigation. C. parvum activates kinase pathways in infected cells (10,11,16); we recently demonstrated that there is recruitment of transporters and channels to the site of infection (15), consistent with the active recruitment of vesicles to the plasma membrane. It therefore seems reasonable that C. parvum-induced initiation of vesicular trafficking and membrane insertion may culminate in the shedding of FasL-bearing membrane in directly infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that C. parvum induces host cell actin rearrangement upon invasion of different cell lines and that this process is necessary for invasion to occur (6,9,12,13).We have previously shown that this also occurs when C. hominis enters HCT-8 cells (17). Our demonstration of the colocaliza- A previous study has shown that treatment of primary bovine fallopian tube epithelial cells with genistein, staurosporine, suramin sodium salt, or wortmannin inhibited entry of C. parvum sporozoites (14).…”
Section: Discussionmentioning
confidence: 99%